The Impact of Social Support on HIV Care, Support, and Treatment (CST) Service Utilization Among Men Who Have Sex with Men (MSM): A Cross-Sectional Study in Medan City - Dhani Syahputra Bukit; Ayudiah Khairani; R Kintoko Rochadi (Journal of Health and Nutrition Research, 2026)
Men who have sex with men (MSM) remain a key population with a heightened risk of HIV infection, underscoring the importance of HIV care, support and treatment (CST) services in improving health outcomes. However, the utilization of CST services among MSM is often hindered by stigma, discrimination, and fear of receiving a positive HIV diagnosis. These barriers highlight the need to understand the role of social support in encouraging service uptake. This cross-sectional study involved 83 MSM in Medan City, selected through purposive accidental sampling. Data were collected using structured questionnaires and analyzed through univariate, chi-square bivariate test, and logistic regression test. The results showed that all assessed forms of social support—emotional, appraisal, informational, and instrumental— were significantly associated with the use of HIV CST Services. Among these, informational support was identified as the most influential factor in increasing service utilization (p=0,007, OR=4,3). In conclusion, informational support plays a dominant role in enhancing the utilization of HIV CST services among MSM. Strengthening the provision of accurate information and guidance is therefore essential in improving service engagement. Recommendations include expanding outreach efforts, enhancing social support mechanisms for MSM, and promoting safe and supportive environment to reduce stigma and encourage access to CST services.